CONSTRUCTION AND VALIDATION OF A FAMILY RESILIENCE SCALE FOR FAMILY MEMBERS OF PEOPLE WITH DISABILITIES IN THE CITY OF ICA.: CONSTRUCCIÓN Y VALIDACIÓN DE UNA ESCALA DE RESILIENCIA FAMILIAR EN FAMILIARES DE PERSONAS CON DISCAPACIDAD DE LA CIUDAD DE ICA - Checcllo Tenorio, Adin Mezollam (2024)
Objective: To create and validate a family resilience in caregivers relatives of people with disabilities (ERF-PD). Method: The research design is instrumental. The sampling was non probabilistic with a sample of 301 relatives of people with disabilities. Initially, 40 items were created but this number was reduced after the statistics analysis. Results: Aiken’s V values of 1.00 were obtained in all items. After the item analysis, nine items were removed. From the exploratory factor analysis, 17 items remained that explain 56.0% of the overall variance; whereas the confirmatory factor analysis obtained good fit indexes for this structure (Chi2/gl=1.876; CFI=0.982; TLI=0.979; RMSEA =0.037; SRMR=0.064). Internal consistency showed coefficients above 0.70 in the general scale and its three factors. Conclusion: The scale shows evidences of validity and reliability for the evaluated sample, justifying its use in research and professional activity.   Keywords: psychometry; resilience; disabled person (source: MeSH NLM)